Business anti-computing: A challenge for organizations - Guardado Lopez, Sinuhe Carlos (2020)
Organizations today have multiple challenges that affect the way and reachment of their objectives. One of these challenges is the correct management of human talent in a vertiginous and turbulent environment. In general, it is considered that the Human Resources area or department adequately performs the various tasks that have been entrusted to it, among them the recruitment and selection of personnel, such activities are essential for the operation of the company. However, some employees act against the interests of the organization and collective, which should disturb organizational managers and Human Resources managers of the companies. The costs of antisocial behaviors within the organization and that the Administration Science has qualified with the name of "anomalous" or "deviated", cost millions of dollars to the companies world. This interdisciplinary manuscript (Neuropsychology, Criminology and Administration Science) scientifically bases antisocial behaviors, their causes and endogenous and exogenous risk factors, which frame the aforementioned behaviors.